Effect of Regular Pilates Exercises on Biomotor and Physiological Parameters in Sedanter Women - Aydemir, İsa; Dağ, Reyhan (İbrahim ERDEMİR, 2021)
Since women are different from men physically and physiologically, it is known that their body weights increase in a shorter time. It is known that excess weight gain negatively affects quality of life and health. However, regular exercises are of great importance in maintaining physical and physiological fitness. From this point of view, in this study; The aim of this study was to investigate the effect of regular pilates exercises on biomotor and physiological parameters in sedentary women. 29 sedentary healthy women who have not done sports before participated in the study. A 12-week pilates exercise program of 60 minutes, 40-60% intensity, 3 days a week, was applied to the participants. In the study, height, body weight, body mass index, flexibility, resting heart rate and fat mass were measured as a pre-test and post-test at the end of 12-week pilates exercises. The pre-test and post-test values of the data obtained from the participants were compared. This comparison was made using the Paired Sample t-test. SPSS package program was used in the analysis of the data. The significance level was set as p

Kadınlar fiziksel ve fizyolojik açıdan erkeklerden farklı olduğu için vücut ağırlıklarının daha kısa sürede arttığı bilinmektedir. Alınan fazla kiloların yaşam kalitesi ve sağlığı olumsuz etkilediği bilinmektedir. Ancak fiziksel ve fizyolojik uygunluğun korunmasında, uygulanan düzenli egzersizler büyük bir önem teşkil etmektedir. Buradan hareketle bu çalışmada; düzenli pilates egzersizlerin sedanter kadınlarda biyomotor ve fizyolojik parametreler üzerine olan etkisinin araştırılması amaçlanmıştır. Çalışmaya sağlıklı daha önce spor yapmamış 29 sedanter kadın katılmıştır. Katılımcılara haftada 3 gün 60 dk’ lık, %40-60 şiddetinde 12 haftalık pilates egzersiz programı uygulanmıştır. Çalışmada ön test ve 12 haftalık pilates egzersizleri sonunda son test olmak üzere boy uzunluğu, vücut ağırlı, vücut kitle indeksi, esneklik, dinlenik kalp atım sayısı ve yağ kütle miktarı ölçümleri yapılmıştır. Katılımcılardan elde edilen verilerin ön test ve son test değerleri karşılaştırılmıştır. Bu karşılaştırma Paired Sample t-testi kullanılarak yapılmıştır. Verilerin analizinde SPSS paket programı kullanılmıştır. Anlamlılık düzeyi p
Düzenli Pilates Egzersizlerinin Sedanter Kadınlarda Biyomotor ve Fizyolojik Parametreler Üzerine Etkisi
Keywords: Sports Medicine; Spor Hekimliği